Ed Ricketts Holds a Jar of Specimens - Peter Stackpole:::Creator::::::::::::
Ed 'Doc' Ricketts standing in Pacific Biological Laboratory, removing one of the jars of specimens from a shelf. See also number 0-522. RESTRICTED USE